PENINGKATAN KEMAMPUAN BERPIKIR KREATIF DAN SELF-EFFICACY SISWA MELALUI PEMBELAJARAN MATEMATIKA REALISTIK - Laili Habibah Pasaribu; Dia Hasanah (JURNAL EDUSCIENCE, 2022)
This research activity is focused on increasing students' creative thinking skills and self-efficacy through realistic mathematics learning (PMR). The type of research used is quantitative research with the method used in this study is a quasi-experimental (quasi-experimental). The instrument used consisted of a creative thinking ability test and a Self-Efficacy. The results showed thatÂ  the value of sig > the significance level was 0.541 > 0.05 then Ho was accepted, which means that there was a significant increase between students' creative thinking abilities and self-efficacy with realistic mathematics learning. Based on research findings that realistic mathematics learning (PMR) can be recommended as one of the learning approaches used in schools primarily to achieve creative thinking competence and Self-Efficacy.